2022
DOI: 10.3389/fmed.2022.833829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Signature Genes and Network of Reactive Oxygen Species Related Genes and DNA Repair Genes in Lung Adenocarcinoma

Abstract: Reactive Oxygen Species (ROS) are present in excess amounts in patients with tumors, and these ROS can kill and destroy tumor cells. Therefore, tumor cells upregulate ROS-related genes to protect them and reduce their destructing effects. Cancer cells already damaged by ROS can be repaired by expressing DNA repair genes consequently promoting their proliferation. The present study aimed to identify the signature genes of and regulating network of ROS-related genes and DNA repair genes in lung adenocarcinoma (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Our experiments also con rm that RRM2 expression is signi cantly higher in LUAD tissues compared to adjacent normal tissues. Cytoplasmic selenoprotein thioredoxin reductase 1 (TXNRD1) plays multiple roles associated with malignant tumors, as it can protect normal cells from malignant transformation [32]. However, in liver cancer, upregulated TXNRD1 expression promotes hepatocellular carcinoma progression through the activation of the Akt/mTOR signaling pathway and is associated with lower patient survival rates [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments also con rm that RRM2 expression is signi cantly higher in LUAD tissues compared to adjacent normal tissues. Cytoplasmic selenoprotein thioredoxin reductase 1 (TXNRD1) plays multiple roles associated with malignant tumors, as it can protect normal cells from malignant transformation [32]. However, in liver cancer, upregulated TXNRD1 expression promotes hepatocellular carcinoma progression through the activation of the Akt/mTOR signaling pathway and is associated with lower patient survival rates [33].…”
Section: Discussionmentioning
confidence: 99%
“…Except for NQO1, the remaining nine candidate mRNAs had a substantial predictive ability. Next, we conducted a literature-based validation of NQO1's prognostic outcome in LUAD (59). We found that NQO1 is a potential therapeutic Glutathione and arachidonic acid metabolic pathways: Red tags showed enriched mRNAs.…”
Section: Biomarkers' Identificationmentioning
confidence: 99%
“…However, due to the absence of survival time or survival status data, some samples were excluded from the study and 746 samples were included in the following analysis 23 . To identify the potential role of ROSRGs in SKCM, a comprehensive list of 260 ROSRGs was compiled using previous research and the Molecular Signatures Database (MSigDB) (Supplementary Table S1) [24][25][26] . The obtained RNA-seq data and clinical information from 8739 samples from 32 types of tumors (excluding acute myeloid leukemia) were acquired from USCS Xena and analyzed to provide a broad perspective on the association between ROSRGs and different forms of cancer 27 .…”
Section: Collection and Organization Of Datamentioning
confidence: 99%